Numerical simulation of debris flow: a case study of the daniao tribe debris flow in eastern taiwan in august, 2009 - Li, Ko-Fei; Hsu, Yu-Charn; Li, Hsin-Chi; Shu, Hung-Ming (Italian journal of engineering geology and environment, 2011)
In August 2009, Typhoon Morakot hit Taiwan and induced tremendous disasters, including large-scale landslides and debris flows. One of these debris flows was suffered by the Daniao tribe in Taitung, eastern Taiwan. The volume was in excesses of 500,000 m3, much larger than the original design mitigation capacity. The DEBRIS-2D program developed by (liu et alii, 2009) was applied in a hazard assessment at this particular site two years before the disaster. The model predicted a hazard zone that was close to the real disaster. This successful prediction seems to support the usefulness of DEBRIS-2D. However, there may be still factors that need to be discussed before identifying the success of the program. One of the important factors discussed was the total volume and its distribution. This paper showed that a 20 % variation in estimating the total volume in this particular site, would give rise to only a 2.75 % variation on the nal front position. Therefore, volume is not very sensitive